A typology of abuses in domestic work in Portugal - Botelho, M.C.; Suleman, F.; Figueiredo, M. C. T. (International Congress on Working Conditions, 2015)
Using an original dataset, our study explores types of abuse and harassment suffered by a sample of domestic workers in Portugal (n=684). Empirical evidence based on multiple correspondence and cluster analyses pointed to three segments of domestic workers: victims of labour abuse related to contract and wages, victims of multiple abuse including mistreatment and also psychological and sexual harassment, and a segment with no occurrence of abuse. Descriptive statistics suggest migrants, especially Brazilian women, prevail in all types of abuse and harassment, but carers of the elderly are often victims of multiple abuse. Domestic workers seem to be protected from the risk of mistreatment by trust related issues and child caring.